Soy milk and avocado juice: what is the best to reduce cholesterol among obesity children? - Rizki Agustin Purwaningtyas; Kustiningsih Kustiningsih (International Journal of Health Science and Technology, 2019)
Children with obesity have high risk to have abnormal cholesterol rate. Obesity and high cholesterol rate can cause cardiovascular disease at a later time. Children have normal rate of cholesterol if the cholesterol rate in the blood is 170 mg/dL, the threshold category between 170-199 mg/dL, and high category is 200 mg/dL. Soy Milk and avocado juice are the ways of non pharmacological care that can be applied to reduce cholesterol rate. This study aims to compare Soy Milk and avocado juice giving toward cholesterol rate in children with obesity in State Elementary School 1 and 2 of Katerban, Central Java Province, Indonesia. The study used quasi experiment design with non-equivalent control group framework. Samples of the study were 30 children taken by use purposive sampling. Soy Milk and avocado juice effective to reduce cholesterol level in obesity children (p value=0,000, p0,05), but neither soy milk and avocado juice there’re no one that more effective to decrease cholesterol level (p value=0,902, p0,05). 60% of respondent were male student age 11 years (36,7%). Father education were high. Soya milk and avocado juice are able to reduce cholesterol rate. Parents must give attention to children’s dietary intake to reduce cholesterol and obesity, also motivate them to do physical activity.